Hyperbilirubinemia as a diagnostic marker for acute appendicitis - Ambre, Sagar Ramesh; Chavan, Shahaji (International Surgery Journal, 2018)
Background: Appendicitis is one of the commonest cause of abdominal pain requiring emergency surgery. Different clinical signs and symptoms always mimic the diagnosis of acute appendicitis with number of causes leading to pain in right iliac fossa, especially in females. Accurate diagnosis can be aided by additional tests. A delay in diagnosis can lead to appendiceal perforation with increased morbidity, and an appendectomy as soon as the condition is suspected, may increase the number of unnecessary appendicectomies. Objective of present study was to evaluate the role of hyperbilirubinemia as a diagnostic marker for Acute Appendicitis. Methods: This is a prospective study of 100 patients carried out at Dr. D.Y. Patil Medical College, Hospital and Research Centre, Pimpri, Pune from May 2015 to September 2017. Patients presenting to surgical OPD with pain in Right iliac fossa will be evaluated. Those with a clinical diagnosis of acute appendicitis will be included in the study. Results: Acute appendicitis is one of the most common emergencies and appendicectomy is one of the most frequently done abdominal operations. Clinical diagnosis using time tested clinical signs is effective in diagnosing appendicitis. However, bilirubin supports diagnosis and hence avoids chances of error in diagnosis. The investigation Bilirubin alone is not sufficient to accurately diagnose acute appendicitis, however the clinical findings, ALVARADO SCORE when combined can predict appendicitis. There is significant difference in total bilirubin in acute and probable cases of appendicitis but it can be used to differentiate both of them. In present study Mean bilirubin for acute appendicitis was 1.23mg/dl and probable cases of appendicitis was 0.84mg/dl, with SD for acute appendicitis was 0.598 and probable cases of appendicitis was 0.486. In our study bilirubin provide the highest diagnostic accuracy for acute appendicitis case. Normal inflammatory markers cannot exclude appendicitis, which remains a clinical diagnosis. The presence of history of pain and or signs of peritoneal inflammation which help you in diagnosing acute appendicitis. Conclusions: Hyperbilirubinemia can be a diagnostic marker for acute appendicitis.